2015
DOI: 10.1038/srep15117
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-regulated cyclic electron flow supplies ATP for nitrogen starvation-induced lipid biosynthesis in green alga

Abstract: We previously showed that both the linear photosynthetic electron transportation rate and the respiration rate dropped significantly during N starvation-induced neutral lipid accumulation in an oil-producing microalga, Chlorella sorokiniana, and proposed a possible role for cyclic electron flow (CEF) in ATP supply. In this study, we further exploited this hypothesis in both Chlorella sorokiniana C3 and the model green alga Chlamydomonas. We found that both the rate of CEF around photosystem I and the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 47 publications
(81 reference statements)
0
41
1
Order By: Relevance
“…It is possible to enhance the lipid content and the production of certain fatty acids in culture by applying different specific abiotic factors, although conditions that yield high lipid content might not be the most favorable for growth [138]. The best well-known strategy to achieve high lipid accumulation in oleaginous microorganisms is through nitrogen starvation [139][140][141][142][143][144][145]. Nitrogen is an essential part of the synthesis of proteins, nucleic acids, and chlorophyll, and during nitrogen limitation, microalgae undergo rapid metabolic remodeling, directing the carbon flow toward lipid production [140,144,[146][147][148][149][150][151][152][153].…”
Section: Oleaginous Microalgae and Diatomsmentioning
confidence: 99%
“…It is possible to enhance the lipid content and the production of certain fatty acids in culture by applying different specific abiotic factors, although conditions that yield high lipid content might not be the most favorable for growth [138]. The best well-known strategy to achieve high lipid accumulation in oleaginous microorganisms is through nitrogen starvation [139][140][141][142][143][144][145]. Nitrogen is an essential part of the synthesis of proteins, nucleic acids, and chlorophyll, and during nitrogen limitation, microalgae undergo rapid metabolic remodeling, directing the carbon flow toward lipid production [140,144,[146][147][148][149][150][151][152][153].…”
Section: Oleaginous Microalgae and Diatomsmentioning
confidence: 99%
“…PGRL1 is a major component of cyclic electron flow in C. reinhardtii and has been proposed to supply additional ATP for photosynthesis, particularly in conditions of high ATP demand (Tolleter et al, 2011;Dang et al, 2014). The PGRL1-deficient mutant (pgrl1) was reported recently to accumulate less neutral lipids under N starvation, and it was suggested that cyclic electron flow supplies ATP for lipid biosynthesis during N starvation (Chen et al, 2015). The association of PGRL1 with LDs of SLexposed cells expands its role in supplying ATP for Only proteins with two or more peptides and two or more specific spectral counts (SSCs) were retained for analyses.…”
Section: Biogenesis and Physiological Functions Of Lds Under Slmentioning
confidence: 99%
“…reinhardtii and Chlorella sp. regulates N starvation-induced neutral lipid by increasing calmodulin activity [82,83]. We suggests that Ca 2+ signal transduction participates in lipid accumulation in haptophytes.…”
Section: How Is Nitrogen Limitation Mediated?mentioning
confidence: 99%